Kajian Heat Shock Protein 90 (HSP90) dalam Pencarian Kandidat Penghambatnya melalui Ekplorasi Bahan Alam Indonesia: Review On Heat Shock Protein 90 (HSP90) for Exploration of Its Inhibitor Candidates through Indonesian Natural Resources - Sitepu, Rehmadanta (Universitas Tadulako, 2019)
Exploration on anticancer candidates on inhibition of Heat Shock Protein (HSP) activity are increasing in the past ten years. Some of HSP90 inhibitor candidates were in third phase of clinical trials. However, this issue is not followed by the emergency of HSP90 inhibitor research in Indonesia, not only study on natural source but also on synthetic candidates. This study aims to look the development of tracking HSP90 inhibitor candidates globally so that it can initiate the related research in Indonesia. Study of HSP90 and its inhibitors were taken from scientific articles in the range from 2009 to 2018. HSP90 and its inhibitors have important values in the dynamics of functions and stability of proteins to maintain survival of cells. This also include the oncogene proteins that involve in cell proliferation such as tyrosine kinases, transcription factors, and regulatory proteins that expression and interaction depend on HSP90. Expression of the transcription factor p53, Alk gene, Wnt gene, glucocorticoid receptors have also links with HSP90 protein activity. Some candidates for inhibitor of HSP90 have been entering clinical trials such as geldanamycin analogues, resorcinol derivatives, and purines analog. Candidates from natural sources that are also being developed such as luteolin, licochalcone A, oleochantal, novobiocin, epigallocathecin gallat, silybin, deguelin, and celastrol from terpenoid class, Apigenin from flavon class, Curcumin, and Gambogat Acid. HSP90 inhibitors which are entering the third phase of clinical trial are ganetespib from the resorcinol derivative and retaspimycin from geldanamisin analog group. Exploration of HSP90 inhibitors from Indonesia natural resources still have great potential to be developed because they have high impact values as anticancer candidates.